Massive presence of off‐label medicines in Danish neonatal departments: A nationwide survey using national hospital purchase data. Issue 1 (21st December 2022) - Gade, Christina; Trolle, Stine; Mørk, Mette‐Louise; Lewis, Anna; Andersen, Peter Fruergaard; Jacobsen, Thorkild; Andersen, Jon; Lausten‐Thomsen, Ulrik
Abstract: There is currently insufficient knowledge of gestational age dependent medicine disposition in neonates. Accordingly, the use of off‐label medication, i.e., use of medicines outside its approved marketing authorization, is high in the neonatal departments. By using data from the Danish National Pharmaceutical Hospital Purchase Database, we identified the most commonly occurring medications and calculated the on/off‐label ratios for premature and term neonates. Data was extracted on ATC level 5 and based on defined daily doses as per WHO. Data covered the 4 high‐level NICUs and 10 of 13 of the intermediate/standard level Danish neonatal departments. Of the identified medication, 87% and 70% did not have approved marketing authorization for use in premature and full‐term neonates, respectively. Furthermore, one‐fifth of the top 100 medicines did not have a (Danish) marketing license. Overall, off‐label medication was widespread covering virtually all ATC groups and no ATC group had an off‐label level lower than 50% (range 50%–100%). Finally, in 21% of medications, additives from 8 different chemical groups with potential deleterious effects for neonates were identified. In conclusion, off‐label medication in the Danish neonatal departments is widespread. The pharmaceutical industry is unlikely to solve this problem, and we may for a very long time be occasionally forced to use off‐label medication. Practical solution must therefore come from multidisciplinary clinical and academic collaboration. Use of formulation list as guidance for prescriptions and NICU‐friendly galenic formulations may mitigate the problem temporarily while waiting for definitive studies. Abstract : Off‐label medications are massively present in the NICUs. As some even contain potential pernicious additives, this puts term and particularely preterm babies at risk of increased risk of adverse or insufficient drug effects. Gade et al. Massive presence of off‐label medicines in Danish neonatal departments . Pharmacol. Res. Perspect 2022.